Differential Comprehensive Effects of Food Quality and ZnO Nanoparticles on the Key Traits of Early Life History of Daphnia magna - Sun, Yunfei; Yu, Bo; Lei, Yulu; Qin, Shanshan; Lyu, Kai; Yang, Zhou (Frontiers in Environmental Science, 2022)
In aquatic ecosystems, cladocerans as an important part of zooplankton are often exposed to new pollutant nanoparticles and poor quality food simultaneously. To evaluate the combined effects of poor quality food and nanoparticles on the development and early reproductive performance of cladocerans, we exposed Daphnia magna, a representative cladocerans, to different concentrations of ZnO nanoparticles under the food conditions containing different proportion of non-toxic Microcystis, recorded some key indicators of the early life history, and analyzed the possible differential dose effects. Results showed non-toxic Microcystis and ZnO nanoparticles significantly delayed the times to maturation and reproduction, and also significantly reduced the survival time, the body length at maturation, the number of offspring in the first brood, and the total offspring per female of D. magna. When the food contained non-toxic Microcystis, D. magna did not reach sexual maturity at 0.25 mg L-1 ZnO nanoparticles and did not develop eggs and reproduce offspring at 0.20 mg L-1 ZnO nanoparticles. Specially, non-toxic Microcystis and ZnO nanoparticles had a significant or nearly significant synergistic effect on the time to maturation, time to first brood, and the total offspring per female of D. magna, whereas for other life history indicators, non-toxic Microcystis and ZnO nanoparticles showed an additive effect, based on comparing the slopes of linear fitting of the relevant indicators with nanoparticle concentration under different food quality conditions. Such findings are helpful to realistically evaluate the comprehensive stress effect on zooplankton under the complex conditions of poor food quality and coexistence of pollutants.